COMPARATIVE ANALYSIS OF STATE ADMINISTRATIONS IN FRANCE AND GERMANY - Totok Minto Leksono; Metasari Putri (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
This article compares German and French public administration, focusing on differences in state form, government system, political system, bureaucratic structure, as well as resource, moral, and economic factors. Germany itself, with its federal system and strong decentralization, contrasts with France which is a unitary state with dominant centralization. The method used is descriptive qualitative with a literature study approach. The difference in the form of the state and the system of government affects the mechanism of decentralization, public service management, and the relationship between the central and local governments, in this case decentralization, Germany shows a high level of regional autonomy through a clear division of authority between the federal government and the states (Lander). The analysis shows that the federal government structure provides flexibility and efficiency in public services, while the unitary model is more centralized and coordinative. The results of this study are expected to contribute to understanding the dynamics of government and its influence on state governance, and become a reference for the formulation of contextual and adaptive public policies in Indonesia.